2003
DOI: 10.1093/jxb/erg092
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of seed ageing under different storage conditions for Vigna radiata (L.) Wilczek: lipid peroxidation, sugar hydrolysis, Maillard reactions and their relationship to glass state transition

Abstract: Two primary biochemical reactions in seed ageing (lipid peroxidation and non-enzymatic protein glycosylation with reducing sugars) have been studied under different seed water contents and storage temperatures, and the role of the glassy state in retarding biochemical deterioration examined. The viability loss of Vigna radiata seeds during storage is associated with Maillard reactions; however, the contribution of primary biochemical reactions varies under different storage conditions. Biochemical deterioratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
141
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(164 citation statements)
references
References 23 publications
5
141
0
4
Order By: Relevance
“…Nagaraj et al 1996). In plants the Maillard reactions products are thought to influence seed colour during aging and are associated with seed viability loss depending on storage conditions (Taylor et al 2000;Murthy et al 2003). The germination delay observed could be due to such events but this is unlikely since the random process of glycoprotein formation would affect cellular processes in general.…”
Section: Discussionmentioning
confidence: 99%
“…Nagaraj et al 1996). In plants the Maillard reactions products are thought to influence seed colour during aging and are associated with seed viability loss depending on storage conditions (Taylor et al 2000;Murthy et al 2003). The germination delay observed could be due to such events but this is unlikely since the random process of glycoprotein formation would affect cellular processes in general.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, even in seeds of high longevity, degenerative processes do occur during long storage, and they include lipid oxidation, membrane and DNA impairments, degradation of proteins and decrease of enzyme activities (Murthy et al 2003). Ageing-related reduction of enzyme activity was observed in enzymes as essential as dehydrogenases of the Krebs cycle, cytochrom c oxidase, and malate and glutamate dehydrogenases.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, according to Gill and Tuteja (2010) (Figures 3 and 4). In this case, the presence of ROSs may arise from non-enzymatic reactions, such as lipid peroxidation and the Amadori and Maillard reactions since the enzyme activity of the antioxidant system is probably reduced in this condition (Murthy et al, 2003). Pukacka and Ratajczak (2005) also found hydrogen peroxide production in dry Fagus sylvatica seeds.…”
Section: Resultsmentioning
confidence: 95%
“…The high moisture content of the seeds associated with the increase in the hydrogen peroxide content compromised the germination process. Okane et al (1996) observed that H 2 O 2 production in calluses of Arabidopsis thaliana plants was greater at 4 °C than at 23 °C. Similar results were found by Sun et al (2010), who observed accumulation of H 2 O 2 in leaf tissue under low temperature conditions in Nicotiana tabacum seedlings.…”
Section: Resultsmentioning
confidence: 96%